Heterogeneity of colorectal cancer risk by tumour characteristics: Large prospective study of UK women - Burón Pust, Andrea (Int J Cancer, 2017)
Associations between behavioural and other personal factors and colorectal cancer risk have been reported to vary by tumour characteristics, but evidence is inconsistent. In a large UK‐based prospective study we examined associations of 14 postulated risk factors with colorectal cancer risk overall, and across three anatomical sites and four morphological subtypes. Among 1.3 million women, 18,518 incident colorectal cancers were identified during 13.8 (SD 3.4) years follow‐up via record linkage to national cancer registry data. Cox regression yielded adjusted relative risks. Statistical significance was assessed using correction for multiple testing. Overall, colorectal cancer risk was significantly associated with height, body mass index (BMI), smoking, alcohol intake, physical activity, parity and menopausal hormone therapy use. For smoking there was substantial heterogeneity across morphological types; relative risks around two or greater were seen in current smokers both for signet ring cell and for neuroendocrine tumours. Obese women were also at higher risk for signet ring cell tumours. For adenocarcinomas, the large majority of colorectal cancers in the cohort, all risk factor associations were weak. There was little or no heterogeneity in risk between tumours of the right colon, left colon and rectum for any of the 14 factors examined. These epidemiological findings complement an emerging picture from molecular studies of possible different developmental pathways for different tumour types.